Saturday

April 19, 2014

April 19, 2014

Posted by **jaton** on Saturday, August 4, 2012 at 12:31am.

- math -
**Bosnian**, Saturday, August 4, 2012 at 1:26amx + 3 y = 7 Subtract 3 y to both sides

x + 3 y - 3 y = 7 - 3 y

x = 7 - 3 y

Put x = 7 - 3 y into equation x + 4 y = 12

7 - 3 y + 4 y = 12

7 + y = 12 Subtract 7 to both sides

7 + y - 7 = 12 - 7

y = 5

Replacing y = 5 into x = 7 - 3 y gives

x = 7 - 3 * 5

x = 7 - 15

x = - 8

**Related Questions**

Algerbra 1 substitution method - im really confused about this question: 2x-3y=...

Linear Equations - Can you please help solve this equation using the ...

math - Can someone please check my work? Solve using substitution method 1. 3x+...

substitution method - solve using the substitution method 6x+2y=-14 -5x+y=25 The...

substitution method - solve using the substitution method 8x -9y= -95 5x+64=y ...

substitution method - solve using the substitution method 8x+6y=8 -9x+y=22 The ...

MATH - SYSTEMS OF EQUATIONS CAN BE SOLVED BY GRAPHING OR BY USING SUBSTITUTION ...

math - Systems of equations can be solved by graphing or by using substitution ...

math - SYSTEMS OF EQUATIONS CAN BE SOLVED BY GRAPHING OR BY USING SUBSTITUTION ...

Algebra - Systems of equations can be solved by graphing or by using ...